Significant gastrointestinal morbidity after sacrocolpopexy: The incidence and risk factors - Jo, Yu Ri (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology; Korean Urogynecologic Society, 2014)
OBJECTIVE: This study aimed to quantify the risk of significant gastrointestinal (GI) morbidity after sacrocolpopexy (SCP), and to identify related risk factors. METHODS: A retrospective study was performed of 258 patients who underwent laparotomic SCP for symptomatic pelvic organ prolapse (POP) from November 2008 to August 2013. By the review of medical records, the frequency of significant GI morbidity that resulted in a prolonged initial hospitalization, readmission, or reoperation was assessed. Thereafter, risk factors for significant GI morbidity were assessed using univariate and multivariate analyses. RESULTS: Ten patients (3.9%) were identified as having significant GI morbidity; nine (3.5%) had a prolonged initial hospital stay or were readmitted for the medical treatment of postoperative ileus and 1 (0.4%) underwent reoperation for small bowel obstruction. The occurrence of significant GI morbidity was significantly associated with patient's age and prior laparotomy. By multivariable logistic regression analysis, age (odds ratio [OR], 1.14; 95% confidence interval [CI], 1.01-1.27; P=0.03) and prior laparotomy (OR, 6.82; 95% CI, 1.37-34.07; P=0.02) were found as independent risk factors for significant GI morbidity. CONCLUSION: One in 25 (3.9%) women after SCP experiences significant GI morbidity. Particularly, women with older age and prior laparotomy have a higher risk for significant GI morbidity. This data will aid preoperative counseling for Korean POP patients undergoing SCP.